The Nexus of CSR and Business Environmental Complexity, Munificence and Dynamism: Theory and Evidence - Yankuo Qiao (Current Aspects in Business, Economics and Finance Vol. 3, 2022)
The CEO-centric influence in firms’ Corporate Social Responsibility (CSR) activities is widely documented in the literature. Provided the self-interest motive of CEO divergent from shareholder value maximization, it would be interesting and of paramount importance to investigate the strategic decisions on stakeholder management made by the CEO facing varied dimensions of business conditions. Building upon agency theory, the paper proposes a theoretical framework to heuristically model and clarify the relationships between firm’s CSR engagements and the three dimensions of business environmental conditions: market complexity, munificence, and dynamism. Furthermore, I empirically measure the market dimensions and test the propositions drawn from the analytical model. Consistent with the theoretical implications, it is found that CEOs tend to invest more in CSR in competitive market, less in CSR when the market is munificent and more in CSR when the market is dynamic and unpredictable. The findings are consistent with previous research and shed light on the value relevance of CSR activities.